A Multi-Biomarker Approach in Assessing the Growth and Physiological Stress in Pangasianodon hypophthalmus under Acute Ammonia Exposure - Felix, Fereena; Balasubramanian, A.; Ramana, T. V.; Anupama, R. R.; Rajani, M.; Sravani, R. S.; Swapna, N. Mohana (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Fish plays a crucial role in the nutritious diet around the world and aquaculture has rapidly grown to meet increasing demand, becoming the fastest-growing food industry. Ammonia is a major toxin in fish production systems. This study was designed to evaluate the impact of ammonia on the growth, haematology and biochemical profile of Pangasianodon hypophthalmus. A total of 96 fish of P. hypophthalmus having total length (24.63±0.94 cm) and weight of (163.43±8.90g) were stocked in 300 litres collapsible tarpaulin tanks with various TAN levels (60,70,80 ppm) and fed with commercial pellet feed @ 2.5% body weight twice a day. In the control, the highest length and weight recorded were 26.12±1.014 cm and 166.82±2.602g, while the lowest were 25.14±0.476 cm and 163.74±0.286g in the 80 ppm. The sub lethal test revealed that SGR and PER decreased with increasing TAN concentration. In contrast, the FCR increased with increasing concentration of TAN from 0 to 80 ppm. Similarly, haematological parameters decreased in fish exposed to ammonia, particularly in the 80 ppm group compared to levels of 70 and 60 ppm. In contrary, TLC showed gradual increase from 60 to 80 ppm compared to control fish. MCV and MCHC also showed an irregular pattern with changes in the Hb and Ht. As the TAN level increased, biochemical parameters were also increased and showed higher value at 80 ppm compared to 60 and 70 ppm. It is concluded that the P. hypophthalmus showed good survival and growth rate up to 60 ppm of TAN.